1975
DOI: 10.1590/1809-43921975051087
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos gerais do pescado no Amazonas

Abstract: A situação do pescado no Estado do Amazonas é analisada, sendo relacionados dados referentes à produção, comercialização, industrialização e consumo deste produto, principalmente na cidade de Manaus. É apresentada uma lista dos peixes de produção significativa e a variação que ocorre durante as épocas de cheia e vazante dos rios. Ainda são discutidos: métodos empregados na pesca, condições e manuseio do pescado desde a sua captura até o mercado consumidor. O sistema de drenagem apresenta-se bem definido nos pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…After 1994, landings were transferred to the Panair Fishing Terminal in Manaus. From 1970 to 1974, data were acquired from the Brazilian Institute of Geography and Statistics, Z‐2 Fishing, Supply Division of Manaus City Council, Commission for Economic Development of Amazonas (CODEAMA), Department of Inspection of Products of Animal Origin (DIPOA), Assistance Plan for Artisanal Fishing (PESCART) and interviews with fishers (Honda et al., 1975). After 1976, data were obtained from interviews with fishers, as activities of research projects: 1976–1978 (Petrere Jr, 1985), 1980 to 1987 (Mérona & Bittencourt, 1988), 1994–1996 (Batista, 1998), 1997–2004 by the Várzea Natural Resource Management Project – ProVárzea (Batista et al., 2012) and 2018–2019 (Matos et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…After 1994, landings were transferred to the Panair Fishing Terminal in Manaus. From 1970 to 1974, data were acquired from the Brazilian Institute of Geography and Statistics, Z‐2 Fishing, Supply Division of Manaus City Council, Commission for Economic Development of Amazonas (CODEAMA), Department of Inspection of Products of Animal Origin (DIPOA), Assistance Plan for Artisanal Fishing (PESCART) and interviews with fishers (Honda et al., 1975). After 1976, data were obtained from interviews with fishers, as activities of research projects: 1976–1978 (Petrere Jr, 1985), 1980 to 1987 (Mérona & Bittencourt, 1988), 1994–1996 (Batista, 1998), 1997–2004 by the Várzea Natural Resource Management Project – ProVárzea (Batista et al., 2012) and 2018–2019 (Matos et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Description and characterization of tambaqui production systems date to the late 1970s and early 1980s (Supporting Information/ Infographic 1). Lovshin, 29 Lovshin et al 30,31 Honda et al 32 Werder & Saint-Paul, 33,34 Goulding & Carvalho, 3 and Saint-Paul 19,20 reported findings on the species' biological characters and farming potentialgrowth rate, feeding habit, and reproductive behaviour-and the near-total dependence on fisheries to meet >95% of market demand in Manaus, Brazil. Neighbouring states supplied the remaining 5% of tambaqui products commercialized in the region.…”
Section: Farming and Produc Tion Sys Temsmentioning
confidence: 99%
“…Los valores reportados para la amazonía (Anexo 2), que es considerada la mayor cuenca hidrográfica y la región más rica en especies de peces en el mundo, variaron de un mínimo de 18,3 kg per capita por año en el interior del estado de Amazonas (Honda et al, 1975) a 294 kg per capita por año para el Alto Solimones (Fabré y Alonso, 1998). Para la ciudad de Manaus, una de las mayores metrópolis da la región, los valores estimados variaron desde 33,7 kg per capita por año (Gandra, 2010) hasta 55 kg per capita por año (Smith, 1979).…”
Section: Síntesis De Los Trabajos Sobre El Consumo De Peces Para La Amazonía Brasileñaunclassified